Efeito de múltiplas entradas no desempenho do hidrociclone HGOT1 - Ullmann, Grégori (2020)
Hydrocyclones are equipment that promotes separation of suspensions by centrifugal force action and are widely used in the industry. Despite its simple geometric features, the swirling flow inside hydrocyclones is highly complex so the use of tools such as computational fluid dynamics (CFD) is fundamental in its analysis. In the scope of research of FEQUI / UFU several works with hydrocyclones have been performed and, among the equipment produced by the researchers the HGOT1 stands out as a device optimized for high separation efficiency at reasonable energy cost. Similarly, in the literature, several works on geometric modifications of hydrocyclones have been conducted, including changes in the shape and quantity of inlets. Thus, the objective of the present work was to numerically evaluate the effect of the insertion of multiple inlets on the flow and particle separation of HGOT1. Six different geometries were created by varying the number of inlets (2 and 3) and their positions along the cylindrical section of the HGOT1 (inlets positioned at the same height, HGOT1-2A and HGOT1-3A, in spiral setting, HGOT1-2AE and HGOT1-3AE and one-sided setting, HGOT1-2AU and HGOT1-3AU). The numerical simulations were conducted in Fluent® software and to determine the appropriate computational mesh resolutions the GCI test was used. Single-phase simulations were performed to evaluate the hydrodynamic variables inherent to separation and then a multiphase model, verified with experimental data from Kyriakidis (2018), was used to predict particle collection efficiencies of 0.5, 2.0, 5.0, 10.0, 15.0 and 20.0μm particles. In the results, there were observed increases in the liquid ratio and in the Euler number for all the proposed geometries; however, it was shown that there is a relationship between the proximity of the feeds and the pressure drop in the equipment. Simulations also indicated that the most pronounced increases in flow velocity occurred in its tangential component for both cylindrical and conical sections. Despite the increase in energy consumption, the high tangential velocity values associated with higher flow symmetry indicated HGOT1-2A as one of the most promising proposed geometries regarding greater separation efficiency. The results of multiphase simulations indicated a satisfactory prediction of separation with the association of LES + mixture models (relative errors between 1.1 and 9.1%). The separation efficiency performed by HGOT1 using phosphate rock was higher than using quartzite due to the difference between the densities of these materials. In addition, the use of two inlets in the HGOT1-2A geometry provided separation increases and the most pronounced increases in particle separation were observed in 5 and 10μm particles (10.95 and 12.02%, respectively) due to the centrifugal field intensification. Therefore, in the light of the numerical results it was possible to conclude that the use of multiple inlets, positioned in the same region of the cylindrical section promoted the intensification of the tangential velocity of the flow, which produced a stronger centrifugal field and separated more particles.